PENERAPAN MODEL PEMBELAJARAN DRILL AND PRACTICE TERHADAP HASIL BELAJAR CHEST PASS PADA PEMAINAN BOLA BASKET (STUDI PADA SISWA KELAS X SMA NEGERI 1 KOTA MOJOKERTO) - SETYA CANDRA, BASUKISNA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Passing is one of the basic movements in the game of basketball and also can help move the ball to another friend. If the game of basketball cannot do right operand, the game is likely not able to run. There are many learning methods are used in order to improve basic motor skills in students passing. But in reality there are many students who have not been able to master the basic motion passing with the method that has been applied by educators. Therefore, other methods are needed that can improve students' ability to master the basic motion of passing in basketball. This study aimed to determine the effect of drill and practice methods in teaching physical education on learning outcomes chest pass in basketball games. This research is quasi experiment with descriptive quantitative approach. Subjects in this study were students of class X SMA Negeri 1 Kota Mojokerto using cluster random sampling technique totaled 37 students. Class is selected into the sample class X-4. Using research instruments pass the test wall. The purpose of this study is to know the improvement of student learning outcomes using drill and practice learning methods on the basis of motion basketball chest pass. Based on the research findings, it is concluded that learning used a drill and practice method gives better impact on learning outcomes chest pass that is equal to 44.45%. Keywords: Motion basic chest pass, drill and practice methods, learning outcomes.